Технологічна переробка полімерних відходів як фактор забезпечення екологічної безпеки - Катунін, Д. О.; Григоров, Андрій Борисович (Яроче́нко Я. В., 2025)
The causes of the emergence of the "Great Pacific Garbage Continent" and promising solutions for reducing its volumes are analyzed. These solutions are in the plane of the implementation of a global comprehensive strategy that provides for interaction between countries, manufacturers and consumers of polymer products. The technology of thermal catalytic pyrolysis is proposed as one of the main methods for increasing the degree of recycling of polymer waste. The presented technology allows producing components of motor and boiler fuels and can be recycled in conditions of direct accumulation of polymer waste.
Keywords: полімерні вироби; відходи споживання; утилізація; переробка; океанічні забруднення